2001
DOI: 10.1046/j.1440-1819.2001.00892.x
|View full text |Cite
|
Sign up to set email alerts
|

A negative component superimposed on event‐related potentials during light drowsiness

Abstract: The present study examined the nature of the negative shift of event-related potential (ERP) recorded during the fully awake state, wakefulness with minor awareness deficit (light drowsiness) and stage 1 of NREM sleep. The cortical responses evoked by two types of auditory stimuli were recorded in nine subjects at the different levels of consciousness described above. A negative component with peak latency of 250-350 msec, N300, was identified in ERP during light drowsiness but not in the fully awake state. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…Recently, Sekine et al . reported that P300 did not change in both amplitude and peak latency even when the awareness of subjects decreased from fully awake to light drowsiness 25 . Taking that result into consideration, we suggested that the changes of P300 during sleep deprivation are not due to drowsiness but due to cognitive decline.…”
Section: Discussionmentioning
confidence: 69%
“…Recently, Sekine et al . reported that P300 did not change in both amplitude and peak latency even when the awareness of subjects decreased from fully awake to light drowsiness 25 . Taking that result into consideration, we suggested that the changes of P300 during sleep deprivation are not due to drowsiness but due to cognitive decline.…”
Section: Discussionmentioning
confidence: 69%
“…A distracting task was also found to increase P3 latencies and decrease amplitude (Shucard et al 2004;Ramirez et al 2005). One study (Sekine et al 2001), however, reported no change in P300 latency and amplitude from fully-awake to light-drowsiness state.…”
Section: Discussionmentioning
confidence: 94%
“…Subjective sleepiness and psychomotor performance were monitored every 20 min from 1000 to 1600 h. During the first 5 min of each 20 min epoch, the Visual Analog Scale (VAS) (Folstein and Luria, 1973), Stanford Sleepiness Scale (SSS) (Hoddes et al, 1973), and Choice Reaction Time (CRT) (Sekine et al, 2001) were applied consecutively.…”
Section: Methodsmentioning
confidence: 99%
“…CRT was used to assess objective psychomotor performance, as reported previously (Sekine et al, 2001). Two different brief tones (2000 and 1000 Hz), each with a duration of 100 ms, were generated by an automatic stimulator (Nihon Kohden SS-1449, Nihon Kohden, Tokyo, Japan) and presented at 60 dB (normal hearing level).…”
Section: Methodsmentioning
confidence: 99%